2017
DOI: 10.1007/s10278-017-0038-7
|View full text |Cite
|
Sign up to set email alerts
|

Automated Segmentation and Quantification of Drusen in Fundus and Optical Coherence Tomography Images for Detection of ARMD

Abstract: Age-related macular degeneration (ARMD) is one of the most common retinal syndromes that occurs in elderly people. Different eye testing techniques such as fundus photography and optical coherence tomography (OCT) are used to clinically examine the ARMD-affected patients. Many researchers have worked on detecting ARMD from fundus images, few of them also worked on detecting ARMD from OCT images. However, there are only few systems that establish the correspondence between fundus and OCT images to give an accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…Quantitative measurements characterizing the health of the RPE and, in particular, the drusen burden can clearly play an important role in better understanding different pathologies and the effects of treatment. A number of different approaches have been proposed to produce automated drusen burden measurements from OCT datasets, 12,[18][19][20][30][31][32] including a few recent algorithms involving aspects of convolutional neural networks. [30][31][32] Although it is difficult to compare precisely the performance of the different algorithms in the literature, at this time, the RPE elevation algorithm commercially available on the Cirrus SD-OCT instrument is clearly the best understood and most widely used one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative measurements characterizing the health of the RPE and, in particular, the drusen burden can clearly play an important role in better understanding different pathologies and the effects of treatment. A number of different approaches have been proposed to produce automated drusen burden measurements from OCT datasets, 12,[18][19][20][30][31][32] including a few recent algorithms involving aspects of convolutional neural networks. [30][31][32] Although it is difficult to compare precisely the performance of the different algorithms in the literature, at this time, the RPE elevation algorithm commercially available on the Cirrus SD-OCT instrument is clearly the best understood and most widely used one.…”
Section: Discussionmentioning
confidence: 99%
“…A number of different approaches have been proposed to produce automated drusen burden measurements from OCT datasets, 12,[18][19][20][30][31][32] including a few recent algorithms involving aspects of convolutional neural networks. [30][31][32] Although it is difficult to compare precisely the performance of the different algorithms in the literature, at this time, the RPE elevation algorithm commercially available on the Cirrus SD-OCT instrument is clearly the best understood and most widely used one. In this study, we evaluated the performance of a novel automated RPE elevation algorithm developed for the Plex Elite SS-OCTA instrument by comparing drusen volume and area measurements to those obtained using the algorithm on the Cirrus SD-OCT instrument, which is the only RPE elevation algorithm cleared by the FDA.…”
Section: Discussionmentioning
confidence: 99%
“…Abb. 2; [22]), Drusen [13,28], die Fovea [14] oder Abhebungen des retinalen Pigmentepithels [25]. Fürdasdiabetische Makulaödem wurde ein analoges Prognosemodell auf Basis von 629 Patienten in der Protocol T-Studie erstellt, das ebenfalls eine hohe Korrelation vom Ausmaß an intraretinaler Flüssigkeit mit der Visusprognose (also dem Visus am Ende der Nachbeobachtungsphase) aufzeigte [11].…”
Section: Detektion Von Strukturenunclassified
“…Related work In recent years, deep learning based and non deep learning based methods were applied on this task [3,4,5,6,7]. Generally it has been shown that deep learning based methods, namely convolutional neural networks (CNN), outperform the previous cost-function based models [3,6,7].…”
Section: Introductionmentioning
confidence: 99%